44. Surround inhibition abnormalities in focal hand dystonia may not depend by alterations in somatosensory integration. Issue 12 (December 2017) - Terranova, C.; Rizzo, V.; Morgante, F.; Maggio, R.; Calamuneri, A.; Girlanda, P.; Quartarone, A.
Abstract : Surround inhibition is a system that sharpens sensation by creating an inhibitory zone around the central core of activation. In the motor system, this mechanism probably contributes to the selection of voluntary movements and seems to be lost in dystonia. To explore if sensory information is abnormally processed and integrated in focal dystonia and if surround inhibition phenomena are operating during sensory-motor plasticity and sensory-motor integration in normal humans and in patients with focal hand dystonia. We looked at motor evoked potential (MEP) facilitation, in the APB and ADM muscles, obtained after 5 Hz repetitive paired associative stimulation, stimulating median (PAS M), ulnar (PAS U) and median + ulnar nerve (PAS MU) in 8 normal subjects and 8 dystonic patients. We evaluated the ratio MU/(M + U) × 100. Moreover, we tested the spatial and temporal somatosensory integration recording SEPs evoked by a dual nerve input. Our data confirmed that in dystonic patients the amount of facilitation was larger than normal subjects and the spatial specificity was lost. The MU/(M + U) × 100 ratio was similar in healthy subjects and in dystonic patients and the somatosensory integration was normal in this subset of patients. These data suggest that lateral surround inhibition phenomena during sensory-motor plasticity are normal in focal hand dystonia.